MENERAPKAN PENDIDIKAN 4.0: INTEGRASI ANALISIS BIG DATA DALAM PENGAMBILAN KEPUTUSAN AKADEMIK - Bella Dinata; Ilham Wahyudi; Diah Fatma; Puja Juwita Kesuma (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research aims to explore how Big Data can increase effectiveness in decision making in the education sector. The method used is a literature study, where data is collected from various trusted sources, such as scientific journals and research reports that specifically discuss the topic of Big Data in education. The data collection stage involves searching, selecting and grouping relevant literature. After the data is collected, analysis is carried out by identifying the main findings that contribute to the research objectives, through steps such as grouping data, presenting data, and drawing conclusions. The research results show that the use of Big Data in education can have a significant impact, both in improving student 2 learning outcomes through personalization and academic monitoring, as well as in supporting more efficient education management through data-based decision making. However, despite the large potential benefits, the application of Big Data in education still faces challenges, such as technological limitations, a lack of experts skilled in data analysis, and resistance to change among educators and management. To overcome this challenge, there is a need to improve technological infrastructure, develop training programs for educators and staff, and apply change management theory to help the transition to a data-based system. In this way, it is hoped that the benefits of Big Data can be optimized to achieve more effective and sustainable educational goals